Birth weight percentiles in Western-Mexico - América Aime Corona-Gutiérrez; Eva Elizabet Camarena-Pulido; Juan Pablo Arellano-Cardenas; Mireya Robledo-Aceves; Claudia Angélica Quezada-Salazar; Larissa María Gómez-Ruíz; Rene Oswaldo Pérez-Ramírez (Instituto Nacional de Salud Pública, 2022)
Not available